2018
DOI: 10.1200/jco.2018.78.7366
|View full text |Cite
|
Sign up to set email alerts
|

Improved Survival by Adding Lomustine to Conventional Chemotherapy for Elderly Patients With AML Without Unfavorable Cytogenetics: Results of the LAM-SA 2007 FILO Trial

Abstract: Purpose Acute myeloid leukemia (AML) in elderly patients has a poor prognosis. In an attempt to improve outcome for these patients, the prospective open-label phase III LAM-SA 2007 (Adding Lomustine to Chemotherapy in Older Patients With Acute Myelogenous Leukemia (AML), and Allogeneic Transplantation for Patients From 60 to 65 Years Old) trial randomly assigned patients to a standard induction regimen with lomustine added or to a consolidation regimen with cytarabine and idarubicin. Patients and Methods Adult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 29 publications
(4 reference statements)
1
39
0
Order By: Relevance
“…3 In addition, elderly patients often present comorbidities and reduced functional reserves, which are associated with increased treatment-related mortality and represent contraindications to the use of intensive chemotherapy (ICT). Consequently, population-based studies have shown that 50% to 70% of elderly patients are not offered ICT, [4][5][6] and those few that are eligible have a generally better outcome [7][8][9] when compared with those deemed unfit for ICT with a median overall survival (OS) of 12 months versus 3 to 10 months, respectively. [10][11][12] However, there have been several advances during the past decade that attempt to address this issue, such as the optimization of ICT regimens 8 and the use of nonmyeloablative conditioning regimens for allogeneic stem cell transplantation (SCT), 13 while the development of therapies utilizing hypomethylating agents (HMAs) has provided an effective alternative to ICT.…”
Section: Introductionmentioning
confidence: 99%
“…3 In addition, elderly patients often present comorbidities and reduced functional reserves, which are associated with increased treatment-related mortality and represent contraindications to the use of intensive chemotherapy (ICT). Consequently, population-based studies have shown that 50% to 70% of elderly patients are not offered ICT, [4][5][6] and those few that are eligible have a generally better outcome [7][8][9] when compared with those deemed unfit for ICT with a median overall survival (OS) of 12 months versus 3 to 10 months, respectively. [10][11][12] However, there have been several advances during the past decade that attempt to address this issue, such as the optimization of ICT regimens 8 and the use of nonmyeloablative conditioning regimens for allogeneic stem cell transplantation (SCT), 13 while the development of therapies utilizing hypomethylating agents (HMAs) has provided an effective alternative to ICT.…”
Section: Introductionmentioning
confidence: 99%
“…Lomustine is an alkylating agent with anti‐leukemic activity . The FILO study group recently reported the significant impact of adding lomustine to idarubicin and cytarabine with a higher response rate and reduction in relapses resulting in better EFS and improved OS . Furthermore, we have been using idarubicin over 5 days for a long time in both younger and older patients based on the pharmacologic properties of this drug .…”
Section: Discussionmentioning
confidence: 99%
“…Obviously, our study has several limitations to make definitive general conclusions. It was retrospective, monocentric and we recognize that our chemotherapy regimen is not broadly used outside centers from the French Innovative Leukemia Organization (FILO) study group . Moreover, despite the selection criteria of CPX‐351 trial, there were significant differences between both studies especially regarding prior exposure to HMA, which should be kept in mind for interpretation of data.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations